Preparation method and application of a multifunctional modified high-efficiency selective heavy metal adsorption material

CN118874430BActive Publication Date: 2026-10-30LISHUI UNIV +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410922312.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-10
Publication Date
2026-10-30
Estimated Expiration
2044-07-10

AI Technical Summary

Technical Problem

然而,传统吸附材料如生物炭,海泡石,沸石等对重金属离子的吸附位点有限,导致吸附容量低,吸附耗时长,吸附过程中几乎没有选择性

Benefits of technology

[0021]1.本发明采用2-甲基丙烯酸羟乙酯作为结构单体,该单体具有的羟基官能团赋予了其出色的亲水性和优良的共聚能力,从而极大地提升了对水中污染物的吸附效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118874430B_ABST
    Figure CN118874430B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and application of a multifunctional modified high-efficiency selective heavy metal adsorption material. The preparation method is as follows: 2-methacrylate hydroxyethyl is used as a synthetic monomer, reacts with benzoyl peroxide and isocyanate to synthesize an intermediate polymer, then ethylenediamine and 2,3-dimercaptosuccinic acid are added to connect various functional groups on the basis of the intermediate polymer, and finally the adsorption material is obtained. The application uses 2-methacrylate hydroxyethyl as a structural monomer, the hydroxyl functional group of the monomer has excellent hydrophilicity and excellent copolymerization capacity, thereby greatly improving the adsorption effect on pollutants in water. In addition, the preparation method is simple, the synthesis condition is mild, the synthesis raw material is green and low in cost, the obtained adsorption material can be applied to high-concentration heavy metal pollution industrial wastewater or low-concentration heavy metal pollution surface water, and the adsorption material can efficiently, quickly and selectively adsorb Cu 2+ Realize adsorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of heavy metal adsorption materials for the removal of heavy metals from surface water, and specifically to a method for preparing and applying a highly efficient and selective heavy metal adsorption material modified with multiple functional groups. Background Technology

[0002] With rapid industrial development, heavy metal pollution of surface water has become a problem that cannot be ignored. Unlike other organic pollutants, heavy metal pollutants typically exist in dissolved form in surface water and are non-degradable, easily accumulating in the aquatic environment. Through bioaccumulation and biomagnification along the food chain, they ultimately cause significant harm to the environment and various organisms. Therefore, heavy metal ions are considered one of the most widespread pollutants in the aquatic environment. Thus, achieving efficient control of heavy metal content in the aquatic environment is particularly important. Currently, the most common heavy metal ions discharged from industrial wastewater into surface water include Cu. 2+ Zn 2+ Pb 2+ and Cd 2+ etc., of which Cu 2+ Cu is highly toxic and readily accumulates in organisms, damaging the immune system and having significant negative effects on the human liver and brain. Therefore, the efficient and rapid removal of Cu from surface water is crucial. 2+ This is worth considering.

[0003] Common methods for removing heavy metal ions include ion exchange, chemical precipitation, biological methods, membrane filtration, and adsorption. Among these, adsorption is widely used due to its ease of operation, cost-effectiveness, and high efficiency. However, traditional adsorbent materials such as biochar, sepiolite, and zeolite have limited adsorption sites for heavy metal ions, resulting in low adsorption capacity, long adsorption time, and almost no selectivity during the adsorption process. Although some new adsorbent materials, such as covalent organic frameworks and metal-organic frameworks, have emerged in recent years, their overall synthesis and preparation processes suffer from drawbacks such as expensive raw materials and complex synthesis procedures. Therefore, developing a highly efficient, selective, and low-cost adsorbent material is crucial for achieving precise control of heavy metal pollution in surface water.

[0004] 2-Hydroxyethyl methacrylate (HEMA) monomers are widely used in the biomedical field due to their low cost, chemical stability, excellent biocompatibility, and non-toxicity. The hydroxyl functional groups in HEMA give it hydrophilicity, making it easy to copolymerize with other monomers and exhibiting good adsorption performance for pollutants in water. Building on this advantage, specific functional groups are grafted onto the monomer to design an adsorbent material with a simple synthesis process, low cost, and high efficiency and selectivity for heavy metal adsorption. This material can then be applied to the removal of heavy metals from surface water and industrial wastewater, achieving precise and efficient control of heavy metal pollution. Summary of the Invention

[0005] The first objective of this invention is to provide a method for preparing and applying a highly efficient and selective heavy metal adsorbent material modified with multiple functional groups. This method has a simple synthesis process, mild reaction conditions, and uses inexpensive and readily available raw material HEMA, which is easy to bind and modify. The prepared adsorbent has high efficiency and high selectivity for heavy metals.

[0006] In a first aspect, the present invention provides a method for preparing a highly efficient and selective heavy metal adsorbent material modified with multiple functional groups, comprising the following steps:

[0007] S1: Hydroxyethyl 2-methacrylate, N,N-dimethylformamide and benzoyl peroxide are added sequentially to the reaction vessel, and the mixture is sealed and reacted for 1-2 hours in a water bath at 60-80℃ to obtain the reaction solution;

[0008] S2: Add isocyanate to the reaction solution obtained in step S1, and react to obtain polymer A;

[0009] S3: Add ethylenediamine to the reaction solution obtained in step S2, and react to obtain polymer B;

[0010] S4: Add 2,3-dimercaptosuccinic acid to polymer B obtained in step S3, and react under sealed stirring at 45℃-65℃ for 2h-5h to obtain the final adsorbent material.

[0011] Preferably, in step S1, the amount of benzoyl peroxide relative to N,N-dimethylformamide is 10 / 9 g / L to 2.5 g / L; and in step S2, the amount of isocyanate relative to N,N-dimethylformamide is 1 / 15 L / L to 1 / 6 L / L.

[0012] Preferably, the reaction conditions in step S1 are: at a temperature of 60℃-80℃, with a stirring rate of 160r / min-180r / min, for 2h-5h.

[0013] Preferably, the reaction conditions in step S3 are: cooling to 50℃-70℃, stirring at a stirring rate of 180r / min-200r / min for 3h-6h.

[0014] Preferably, post-processing is performed after the reaction in step S4. The post-processing procedure is as follows: after the reaction solution is cooled, it is filtered, the product is washed with N,N-dimethylformamide and deionized water, and the resulting solid product is dried in an oven at a temperature of 60℃-90℃.

[0015] Preferably, steps S1 to S3 are all performed in a sealed environment.

[0016] Preferably, the molar ratio of 2-hydroxyethyl methacrylate added in step S1, ethylenediamine added in step S3, and 2,3-dimercaptosuccinic acid added in step S4 is (1-3):(1-3):(1-3).

[0017] Secondly, the present invention provides a highly efficient and selective heavy metal adsorbent material modified with multiple functional groups, which is prepared by the aforementioned preparation method.

[0018] Thirdly, the present invention provides the application of the aforementioned highly efficient and selective heavy metal adsorbent material modified with multiple functional groups in the treatment of industrial wastewater and surface water pollution containing heavy metal ions.

[0019] Preferably, the heavy metal ion is Cu. 2+ .

[0020] Compared with existing technologies, this invention demonstrates significant advantages:

[0021] 1. This invention uses hydroxyethyl 2-methacrylate as a structural monomer. The hydroxyl functional group of this monomer endows it with excellent hydrophilicity and good copolymerization ability, thereby greatly improving the adsorption effect on pollutants in water.

[0022] 2. By specifically introducing ethylenediamine and 2,3-dimercaptosuccinic acid, this invention successfully introduces three functional groups—amine, thiol, and carboxyl—into the adsorbent material. This design not only enhances the material's adhesion to heavy metal ions such as Cu 2+ The adsorption efficiency and selectivity are also significantly improved, which also significantly increases the adsorption rate.

[0023] 3. The adsorbent material of this invention can adapt to various polluted environments, ranging from high-concentration industrial wastewater to low-concentration heavy metal-contaminated surface water. The preparation method of this adsorbent material is simple, the reaction conditions are mild, the raw materials used are economical and readily available, and the entire synthesis process is safe and requires no special equipment, making it highly promising for application and worthy of widespread adoption. Attached Figure Description

[0024] Figure 1 These are physical images of the products prepared in Examples 3, 6 and 9 of the present invention.

[0025] Figure 2 These are SEM images of the products prepared in Examples 3, 6 and 9 of this invention.

[0026] Figure 3 The image shows the XRD pattern of the product prepared in Example 3 of this invention.

[0027] Figure 4 The product prepared in Example 3 of this invention is related to Cu. 2+ Zn 2+ Pb 2+ and Cd 2+ Selectivity comparison diagram of mixed metal solutions; where part a corresponds to adsorption capacity and part b corresponds to partition coefficient.

[0028] Figure 5 The product prepared in Example 3 of this invention is related to Cu. 2+ and Cd 2+ The adsorption isotherm diagram is shown; where part a corresponds to the adsorption equilibrium curve and part b corresponds to the removal rate.

[0029] Figure 6 The product prepared in Example 3 of this invention is related to Cu. 2+ and Cd 2+ The adsorption kinetics curve.

[0030] Figure 7 The product prepared in Example 3 of this invention is related to Cu. 2+ and Cd 2+ XPS spectra before and after adsorption. Detailed Implementation

[0031] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments, but the scope of protection of the present invention is not limited thereto.

[0032] Example 1

[0033] A method for preparing a highly efficient and selective heavy metal adsorbent material modified with multiple functional groups, the process of which is as follows:

[0034] Under water bath conditions, 1.625 mL of hydroxyethyl 2-methacrylate (HEMA) was added to a 250 mL three-necked flask and dissolved in 80 mL of N,N-dimethylformamide (DMF). Then, 150 mg of benzoyl peroxide (BOP) was added. The entire system was reacted at 180 rpm in an 80 °C water bath for 1 h under sealed conditions. After the reaction, 8 mL of isocyanate (MDI) was added to the three-necked flask, and the reaction was carried out under the same conditions for 4 h.

[0035] After the above reaction was completed, 0.833 mL of ethylenediamine was added, and the temperature of the synthesis system was lowered to 70 °C, with the reaction proceeding for 4 h. Subsequently, 2.5 g of 2,3-dimercaptosuccinic acid (DMSA) was added, and the reaction was stirred at 60 °C for 4 h, ensuring that the molar ratio of HEMA, ethylenediamine, and DMSA in the synthesis system was 1:1:1. Throughout the synthesis process, the reaction was kept as sealed as possible to minimize the impact of air entering the system on the reaction rate. After the reaction was completed, the prepared material was placed in a 60 °C vacuum drying oven until dried to obtain a solid material. After grinding, the multifunctional modified adsorbent material PFG-HEMA-1 was obtained.

[0036] Example 2

[0037] A method for preparing a highly efficient and selective heavy metal adsorbent material modified with multifunctional groups is disclosed. The difference between this embodiment and Example 1 is only that 3.25 mL of HEMA and 1.666 mL of ethylenediamine are added, resulting in a molar ratio of HEMA, ethylenediamine, and DMSA of 2:2:1 in the synthesis system. The obtained product is PFG-HEMA-2.

[0038] Example 3

[0039] A method for preparing a highly efficient and selective heavy metal adsorbent material modified with multifunctional groups is disclosed. The difference between this embodiment and Example 1 is only that 5 mL of HEMA and 2.50 mL of ethylenediamine are added, resulting in a molar ratio of 3:3:1 for HEMA, ethylenediamine, and DMSA in the synthesis system. The obtained product is PFG-HEMA-3.

[0040] Example 4

[0041] A method for preparing a highly efficient and selective heavy metal adsorbent material modified with multiple functional groups, the process of which is as follows:

[0042] Under water bath conditions, 1.625 mL of HEMA was added to a 250 mL three-necked flask and dissolved in 70 mL of N,N-dimethylformamide (DMF). Then, 150 mg of benzoyl peroxide (BOP) was added. The entire system was reacted at 200 rpm in a 70 °C water bath for 1 h under sealed conditions. After the reaction, 8 mL of isocyanate (MDI) was added to the three-necked flask, and the reaction was carried out under the same conditions for 3 h.

[0043] After the above reaction was completed, 0.833 mL of ethylenediamine was added, and the synthesis system was cooled to 60 °C and reacted for 3 h. Subsequently, 2.5 g of 2,3-dimercaptosuccinic acid was added, and the reaction was stirred at 50 °C for 4 h to achieve a molar ratio of HEMA, ethylenediamine, and DMSA of 1:1:1 in the synthesis system. The entire synthesis process was carried out in a sealed environment to minimize the impact of air on the reaction rate. After the reaction was completed, the prepared material was placed in a vacuum drying oven at 70 °C until it was dried to obtain a solid material. After grinding, the multifunctional modified adsorbent material PFG-HEMA-4 was obtained.

[0044] Example 5

[0045] A method for preparing a highly efficient and selective heavy metal adsorbent material modified with multifunctional groups is disclosed. The difference between this embodiment and Example 4 is only that 3.25 mL of HEMA and 5.0 g of DMSA are added, resulting in a molar ratio of HEMA, ethylenediamine, and DMSA of 2:1:2 in the synthesis system. The obtained product is PFG-HEMA-5.

[0046] Example 6

[0047] A method for preparing a highly efficient and selective heavy metal adsorbent material modified with multifunctional groups is disclosed. The only difference between this embodiment and Example 4 is that 5 mL of HEMA and 7.5 g of DMSA are added, resulting in a molar ratio of 3:1:3 for HEMA, ethylenediamine, and DMSA in the synthesis system. The obtained product is PFG-HEMA-6.

[0048] Example 7

[0049] A method for preparing a highly efficient and selective heavy metal adsorbent material modified with multiple functional groups, the process of which is as follows:

[0050] Under water bath conditions, 1.625 mL of HEMA was added to a 250 mL three-necked flask and dissolved in 80 mL of N,N-dimethylformamide (DMF). Then, 120 mg of benzoyl peroxide (BOP) was added. The entire system was reacted at 200 rpm in an 80 °C water bath for 1 h under sealed conditions. After the reaction, 6 mL of isocyanate (MDI) was added to the three-necked flask, and the reaction was carried out under the same conditions for 4 h.

[0051] After the above reaction was completed, 0.33 mL of ethylenediamine was added, and the synthesis system was cooled to 70 °C and reacted for 3 h. Subsequently, 2.5 g of 2,3-dimercaptosuccinic acid was added, and the reaction was stirred at 60 °C for 4 h to achieve a molar ratio of HEMA, ethylenediamine, and DMSA of 1:1:1 in the synthesis system. The entire synthesis process was carried out in a sealed environment to minimize the impact of air on the reaction rate. After the reaction was completed, the prepared material was placed in an 80 °C vacuum drying oven until it was dried to obtain a solid material. After grinding, the multifunctional modified adsorbent material PFG-HEMA-7 was obtained.

[0052] Example 8

[0053] A method for preparing a highly efficient and selective heavy metal adsorbent material modified with multifunctional groups is disclosed. The difference between this embodiment and Example 7 is only that the amount of ethylenediamine added is 1.666 mL and DMSA is 5 g, resulting in a molar ratio of HEMA, ethylenediamine, and DMSA of 1:2:2 in the synthesis system. The obtained product is PFG-HEMA-8.

[0054] Example 9

[0055] A method for preparing a highly efficient and selective heavy metal adsorbent material modified with multifunctional groups is disclosed. The difference between this embodiment and Example 7 is only that the amount of ethylenediamine added is 2.50 mL, and the amount of DMSA is 7.5 g, resulting in a molar ratio of HEMA, ethylenediamine, and DMSA of 1:3:3 in the synthesis system. The obtained product is PFG-HEMA-9.

[0056] Example 10

[0057] A method for treating heavy metal ion wastewater, the process is as follows:

[0058] 0.05 g of PFG-PHEMA-3 prepared in Example 3 was added to 50 mL of mixed heavy metal solutions (Cu) with concentrations of 10, 20, 50, 100, 150, and 200 mg / L, respectively. 2+ Pb 2+ Cd 2+ and Ni 2+ In the process of adsorption, the solution was shaken at room temperature (25℃) for 3 hours until adsorption was complete. An appropriate amount of the supernatant was then filtered through a 0.45 μm filter membrane. The filtered supernatant was diluted, and the heavy metal concentration was determined using ICP-OES. Subsequently, the concentrations of Cu at different concentrations were calculated. 2+ Pb 2+ Cd 2+ and Ni 2+ The adsorption capacity. Based on this, the adsorption capacity of the adsorbent material for the mixed metal solution is plotted. Figure 4 (part a) and allocation coefficient ( Figure 4 (Part b).

[0059] Example 11

[0060] A method for treating heavy metal ion wastewater, the process is as follows:

[0061] 0.05 g of the PFG-PHEMA-3 prepared in Example 3 was added to 50 mL of Cu 2+ and Cd 2+ In a single-metal system, the initial concentrations of the two metal ions were 50, 100, 200, 300, 400, 500, 600, 700, and 800 mg / L, respectively. After shaking for 3 hours at room temperature (25℃) until adsorption was complete, a suitable amount of the supernatant was filtered through a 0.45 μm filter membrane. The filtered supernatant was diluted, and the heavy metal concentration was determined using ICP-OES. The Cu concentration was calculated. 2+ and Cd 2+ The equilibrium concentration, adsorption capacity, and removal rate of Cu were determined. A plot of Cu was generated based on the experimental data. 2+ and Cd 2+ Adsorption isotherm curves on PFG-PHEMA ( Figure 5 Part a) and the removal rate change graph ( Figure 5 (Part b).

[0062] Example 12

[0063] A method for treating heavy metal ion wastewater, the process is as follows:

[0064] 0.05 g of PFG-PHEMA-3 prepared in Example 3 was added to 50 mL of Cu and Cd solutions with a concentration of 200 mg / L, respectively. The solutions were shaken at room temperature (25 °C), and samples were taken sequentially at shaking intervals of 1 min, 2 min, 5 min, 10 min, 20 min, 30 min, 50 min, 1 h, 2 h, 3 h, 4 h, 5 h, and 6 h. The solutions were filtered through a 0.45 μm filter membrane, and the supernatant was diluted. The heavy metal concentrations were then determined using ICP-OES. Based on the measured Cu... 2+ and Cd 2+ Adsorption kinetic curves of the two metals were plotted at their respective concentrations. Figure 6 ).

[0065] The highly efficient and selective heavy metal adsorbents with multifunctional modifications prepared in Examples 1-9 are organic polymers prepared by crosslinking 2-hydroxyethyl methacrylate monomers as structural units under conditions of N,N-dimethylformamide, benzoyl peroxide, and isocyanate as raw materials. By modifying the polymer, specifically adding amine, carboxyl, and thiol groups, multifunctional modified polyhydroxyethyl methacrylate organic polymers are formed. Figure 1 The images show the synthesized products of the adsorbent material under three different ratios and synthesis conditions. Figure 2 The images show the morphological features of the external particles of the products prepared in Examples 3, 6, and 9 under a scanning electron microscope.

[0066] like Figure 2 As shown, PFG-PHEMA-3 exhibits a rough surface with numerous small, irregularly shaped particles and a variety of pores on a large scale. Small-scale SEM observations reveal these pores forming adsorption channels. PFG-PHEMA-6 also shows a rough surface on a large scale, but with some smooth particles around its periphery. On a small scale, the material appears aggregated with numerous pores. PFG-PHEMA-9 shows a smoother surface on a large scale with clearly defined particles, while small-scale observations reveal a few pores. All three materials exhibit no obvious particle structure, significant surface aggregation, and a clear distribution of surface pores. These adsorption channels provide a large area of ​​exposed functional groups, facilitating the adsorption of heavy metal ions. This porous morphology provides sufficient adsorption space for subsequent adsorption.

[0067] like Figure 3 As shown, the diffraction pattern of this polymer at 2θ = 20.82° is clearly a broad halo, indicating that it has an amorphous structure. The broad peaks in this spectrum are mainly due to the lack of a long-range crystal structure with finite size. This synthetic copolymerization process may interfere with the formation of any regular pattern, resulting in an amorphous homopolymer structure, which also makes it easier for heavy metal ions to enter the interior for adsorption.

[0068] like Figure 4 As shown, the adsorption of all four metals increased under different mixed metal concentrations, especially Cu. 2+ When the initial concentration was 10 mg / L, the adsorption capacities of the four metal ions remained essentially at the same level, indicating that the adsorption sites on PFG-PHEMA-3 were sufficient to allow non-competitive adsorption of low concentrations of metal ions. The partition coefficient (Kd) is typically used to evaluate selective adsorption. Figure 4 b). Although Cu 2+ Cd 2+ and Ni 2+ The adsorption amounts are basically the same, but Cu 2+ K d The value is much higher than that of other metals, indicating that the competition between metal ions and adsorption sites is most intense at this concentration. A comparison of the K values ​​of the four metals at different mixed metal concentrations... d Values ​​(except for mixed metal concentrations of 10 mg·L⁻¹), Cu 2+ K d Its value is 5-8 times that of other metals, followed by Cd. 2+ Ni2+ and Pb 2+ This indicates that PFG-PHEMA-3 affects Cu 2+ It has good selectivity.

[0069] like Figure 5 As shown, 0.05g of the product prepared in Example 3 was added to Cu at different initial concentrations. 2+ and Cd 2+ In solution, as the initial concentrations of both gradually increase, PFG-PHEMA-3 has an effect on Cu 2+ and Cd 2+ The maximum adsorption capacities were 500.0 and 384.6 mg / g, respectively. Meanwhile, the adsorbent materials prepared at low concentrations showed good adsorption for Cu. 2+ and Cd 2+ The removal rates were 91.2% and 79.5%, respectively; however, when the metal concentration increased to 800 mg / L, the removal rates of both decreased to 54.8% and 39.9%, which can be mainly attributed to the excessive free metal ions in the system leading to adsorption saturation of the adsorbent material.

[0070] like Figure 6 As shown, 0.05g of the product prepared in Example 3 was added to 200mg / L Cu 2+ and Cd 2+ In solution, it exhibits a relatively fast adsorption rate, and the two metals can reach adsorption equilibrium within 50 minutes.

[0071] like Figure 7 As shown, 0.05g of the product prepared in Example 3 was added to 200mg / L Cu 2+ and Cd 2+ XPS curve changes of PFG-PHEMA-3 before and after adsorption in solution. Figure 7 Part a demonstrates the adsorption of Cu by PFG-PHEMA-3 prepared in Example 3. 2+ and Cd 2+ The XPS spectrum showed significant changes after adsorption; however, the O1S spectrum did not show significant changes before and after the adsorption of the two metal ions. Figure 7 Part b; the N1s spectrum shows that the PFG-PHEMA-3 prepared in Example 3 adsorbed Cu. 2+ and Cd 2 + Subsequently, the two peaks shifted slightly, and a new peak appeared in the N1s spectrum of PFG-PHEMA-Cd, indicating that the amino groups mainly participated in the Cd synthesis. 2+ The adsorption process, such as Figure 7 The c-part; the S2p spectrum shows that the PFG-PHEMA-3 prepared in Example 3 adsorbed Cu.2+ and Cd 2+ Subsequently, a significant shift in the S2p peak was observed, particularly in Cu. 2+ The shift towards higher binding energies is very significant, indicating that PFG-PHEMA significantly enhances the binding energy of Cu. 2+ The efficient and selective adsorption of S by Cu is also evident. Furthermore, the Cu peak at a binding energy of 162.3 eV indicates the efficient and selective adsorption of S by Cu. 2+ Chemical bonds are formed between them, such as Figure 7 The d-part further demonstrates the effectiveness of the multifunctional modified adsorbent material for Cu. 2+ Highly efficient and selective adsorption.

[0072] By combining the adsorption isotherm curves and adsorption selectivity plots, it can be found that the prepared adsorbent material exhibits good adhesion to Cu. 2+ and Cd 2+ It can achieve rapid and efficient adsorption in a short time, exhibiting excellent adsorption rate, adsorption capacity, and adsorption to Cu. 2+ The excellent selectivity further demonstrates that the prepared adsorbent material is effective against high or low concentrations of Cu in the environment. 2+ Pollution control has promising application prospects.

Claims

1. A highly efficient and selective heavy metal adsorbent material modified with multiple functional groups selectively adsorbs Cu in water containing mixed heavy metal ions. 2+ Applications; characterized in that, Water bodies containing mixed heavy metal ions include Cu 2+ Pb 2+ Cd 2+ and Ni 2+ ; The highly efficient and selective heavy metal adsorbent material modified with multifunctional groups was prepared by the following method: S1: 2-hydroxyethyl methacrylate, which serves as the structural monomer, along with N,N-dimethylformamide and benzoyl peroxide, are added sequentially to the reaction vessel. The mixture is then sealed and reacted in a water bath at 60-80°C for 1-2 hours to obtain the reaction solution. S2: Add isocyanate to the reaction solution obtained in step S1, and react to obtain polymer A; S3: Add ethylenediamine to the reaction solution obtained in step S2, and react to obtain polymer B; S4: Add 2,3-dimercaptosuccinic acid to polymer B obtained in step S3, and react under sealed stirring at 45℃-65℃ for 2h-5h to obtain the final adsorbent material; The molar ratio of 2-hydroxyethyl methacrylate added in step S1, ethylenediamine added in step S3, and 2,3-dimercaptosuccinic acid added in step S4 is 3:3:

1. After the reaction in step S4 is completed, post-processing is performed. The post-processing process is as follows: after the reaction solution is cooled, it is filtered, the product is washed with N,N-dimethylformamide and deionized water, and the obtained solid product is dried in an oven at a temperature of 60℃-90℃.

2. The application according to claim 1, characterized in that: In step S1, the amount of benzoyl peroxide relative to N,N-dimethylformamide is 10 / 9 g / L to 2.5 g / L; in step S2, the amount of isocyanate relative to N,N-dimethylformamide is 1 / 15 L / L to 1 / 6 L / L.

3. The application according to claim 1, characterized in that: The reaction conditions in step S1 are: at a temperature of 60℃-80℃, with a stirring rate of 160r / min-180r / min, for 2 hours.

4. The application according to claim 1, characterized in that: The reaction conditions in step S3 are: cooling to 50℃-70℃, stirring at a stirring rate of 180 r / min-200 r / min for 3h-6h.

5. The application according to claim 1, characterized in that: Steps S1 to S3 all occur in a sealed environment.

Citation Information

Patent Citations

  • Polyurea type anti-settling agent

    CN104497684A

  • Magnetic acrylic-acid polyamine resin capable of removing heavy metal ions and preparation method thereof

    CN105461846A

  • Lead ion adsorbent and preparation method thereof

    CN108404892A